Model Evaluasi Perangkat Lunak: Pemodelan Visual Berbasis Open Source - Harijanto Pangestu (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Visual modeling softwares are numerously available based on both open source and proprietary. However, the softwares are not easy to use and tools available are so confusing for users. Therefore, the evaluation model is needed to choose the proper software. The purpose of this study is to create a model to evaluate the visual modeling software from the user interface and usability. Studied softwares are open source-based because they can be obtained easily for free. The softwares are Umleditor, Umlpad, Violet UML editor, ArgoUML, HE, StarUML, UMLet, Winbrello. This evaluation model is also able to evaluate other softwares. This evaluation uses DECIDE framework which is a guiding framework for evaluation. Evaluation approaches and techniques used are GOMS approach. The final results of this study is an evaluation model that provides software recommendations, namely UMLet 9.1 as well as one which has good usability, like effectiveness, safety, good utility, learnability, memorability, although for efficiency it gets the second place compared to DIA.